The predictive power of the user cost spread for economic recession in China and the US - Dongfeng Chang; Ryan S. Mattson; Biyan Tang (International Journal of Financial Studies, 2019)
The predictive power of the yield curve slope, or the yield spread is well established in the United States (US) and European Union (EU) countries since 1998. However, there exists a gap in the literature on the predictive power of the yield spread on the Chinese economy. This paper provides a different leading recession indicator using the Chinese and US economy as comparative examples: the user cost spread, being the difference of the opportunity costs of holding government securities of different maturities. We argue that the user cost spread, based on the Divisia monetary aggregate data like the ones produced by the Center for Financial Stability, provides improved predictive ability and a better intuitive explanation based on changes in the user cost price of holding bonds.
Keywords: E32; E37; E43; E50; 330; Divisia monetary aggregates; user cost spread; recession; China; yield spread